2018
DOI: 10.1073/pnas.1718945115
|View full text |Cite|
|
Sign up to set email alerts
|

Limiting global-mean temperature increase to 1.5–2 °C could reduce the incidence and spatial spread of dengue fever in Latin America

Abstract: SignificanceThis study is a multigeneral circulation model, multiscenario modeling exercise developed to quantify the dengue-related health benefits of limiting global warming to 1.5–2.0 °C above preindustrial levels in Latin America and the Caribbean. We estimate the impact of future climate change and population growth on the additional number of dengue cases and provide insights about the regions and periods most likely affected by changes in the length of the transmission season. Here, we show that future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 51 publications
1
49
0
2
Order By: Relevance
“…[ 123 ] With the advent of global warming, the global mean temperature has been predicted to increase by another 1.5–2 °C by the end of this century. [ 124 ] The impact of extreme temperature on soil mineralization has also been investigated in vitro. These environment disturbances affect soil mineralization as a result of changes in microbial community activity.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…[ 123 ] With the advent of global warming, the global mean temperature has been predicted to increase by another 1.5–2 °C by the end of this century. [ 124 ] The impact of extreme temperature on soil mineralization has also been investigated in vitro. These environment disturbances affect soil mineralization as a result of changes in microbial community activity.…”
Section: Microbe‐mediated Mineralization In Naturementioning
confidence: 99%
“…The underlying drivers of dengue transmission have been investigated previously and include increased air travel and trade and urban crowding [4,5]. The impacts of weather conditions on dengue occurrence is attracting extensive interest among the research community and policy makers, especially in the context of climate change [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing epidemiological and experimental evidence points to a link between outdoor temperature and dengue incidence [6,[10][11][12][13][14]. The exposure-response association between temperature and dengue incidence is characterised as a bell shape, with the risk of dengue peaking at an optimal temperature, also referred to as the inflection point [11,14].…”
Section: Introductionmentioning
confidence: 99%
“…Modeling studies have anticipated climate-driven emergence of dengue and chikungunya at higher latitudes [50,51] and higher elevations [52,53], and predicted the potential ongoing global expansion of Zika [10,44]. The majority of research at global scales [10,21,54] and in North America and Europe [55] has suggested that climate change is likely to increase the global burden of dengue and chikungunya, and therefore, that mitigation is likely to benefit global health [22,56]. Aedes-borne virus expansion into regions that lack previous exposure is particularly concerning, given the potential for explosive outbreaks when arboviruses are first introduced into naïve populations, like chikungunya and Zika in the Americas [57].…”
Section: Discussionmentioning
confidence: 99%